Patient Uptake, Experiences, and Process Evaluation of a Randomized Controlled Trial of Internet-Based Cognitive Behavioral Therapy for Tinnitus in the United States - Beukes, Eldre W.; Andersson, Gerhard; Manchaiah, Vinaya (Frontiers in Medicine, 2021)
Introduction: Internet-based cognitive behavioral therapy (ICBT) offers a way to increase access to evidence-based tinnitus care. To increase accessibility of this intervention the materials were translated into Spanish to reach Spanish speakers. A clinical trial indicated favorable outcomes of ICBT for a tinnitus for a US population. In view of later dissemination, a way to increase the applicability of this intervention is required. Such understanding is best obtained by considering participant’s perspectives and experiences of an intervention. The objective of the present study was to identify processes that could facilitate or hinder clinical implementation of ICBT in the US. Methods: This study evaluated processes regarding enrolment, allocation, intervention delivery, the outcomes obtained and the trial implementation. The study sample consisted of 158 participants who were randomly assigned to the experimental and control group. Results: Recruiting Spanish participants and participants belonging to ethnic minority groups was difficult despite using a wide range of recruitment strategies. Allocation processes were effective in successfully randomizing the groups. The intervention was delivered as planned, but not all participants chose to engage with the materials provided. Outcomes were favorable, but compliance for completing the outcome measures was low. Personal and intervention factors were identified as barriers for implementation whereas facilitators included the support received, being empowering, the accessibility of the intervention and its structure. Conclusion: An understanding regarding the factors contributing to the outcomes obtained, barriers and facilitators of the results, engagement and compliance were obtained. These insights will be helpful in preparing for future dissemination of such interventions. Clinical trial registration ClinicalTrials.gov: NCT04004260. Registered on 2 July 2019